Monthly and Yearly Standards of Performance for Department Stores: 1930 (Book). - Schmale, Carl N. (The Accounting Review, 1932)
Reviews the book "Monthly and Yearly Standards of Performance for Department Stores: 1930," vol. 3, no. 4, by Edgar H. Gault.